Investigation of effective on-site detention pond design using various methods - Shirline, Leong Ai Lin (2019)
Flash flood and monsoon flood are very common disasters that caused by improper stormwater management. Hence, on-site detention facility plays an indispensable role in stormwater management efforts to reduce probability of flood occurrences. Prior designing on-site detention facility, collection of sufficient time series precipitation data and rainfall data analysis play indispensable role in ensuring the accuracy of on-site detention facility design. In this study, time series rainfall data for the past 30 years were collected and rainfall data gaps were approximated using the Arithmetic Mean method and the consistency of the gap filled rainfall data was evaluated using the Mass Curve method. From the consistency analysis, it was found that Pekan development site has the highest rainfall data consistency followed by Kuantan development site and Jerantut development site. Moreover, the characteristics of on-site detention system is depending on the IDF curve performance which gives the magnitude of rainfall intensity corresponding to various storm duration and ARI. The IDF curves provided in MSMA 2 was not up to the current year. Thus, in this study, IDF curves were developed using Gumbel Type I distribution for the nearest rainfall station to each development site. It was noticed that difference between the study’s IDF curve and MSMA 2 IDF curve appeared to be small for the first 60 minutes of storm duration and gradually increased when the storm duration greater than 60 minutes. This was due to rainfall data considered in developing new IDF curve was only up to 60 minutes. Furthermore, the adoption of on-site detention facility design method determines the cost effectiveness and usefulness of the on-site detention facility. An under designed on-site detention facility has low effectiveness in reducing flood probability whereas an over designed on-site detention facility is not economical. Thus, in this study, on-site detention facility of three development areas were analysed using two methods namely, the Simplified Method and the Modified Puls Method. From the study outcome, it was found that the Modified Puls Method produced more economical design compared to the Simplified Method. Ultimately, the study outcome has provided the civil engineering industry an insight on the cost effective design method of on-site detention facility to prevent monetary losses in construction of oversized on-site detention facility.